Hyoid bone position in relation to Mandibular rotation (Mustansiria Dental Journal, 2018)
Aims This retrospective cephalometric study was designed to evaluate and correlatethe hyoid bone position and angulations in two groups of subjects exhibitingvertical and horizontal mandibular rotation.Material & method: Each group consisted of 50 subjects (25 males and 25 females)with skeletal class I pattern. Cephalometric data were obtained and fourmeasurements were used to locate the hyoid bone in 3 aspects 1. Vertical, 2.Horizontal and 3. Angular. Thirteen angular and linear measurements were usedto evaluate mandibular rotation and facial morphology.Result: There were statistically significant differences in vertical position, horizontaldistances and angulations of hyoid bone measurements between the vertical andhorizontal group subject (P